Memory, identity, and nationalism in European regions - Apryščenko, Viktor Jurʹevič 1976-; Karnaukhova, Oxana (IGI Global, 2019)
"This book sheds light on the evolution of memory, identity, and nationalism of countries in the European region. It also explores the urgency of memory and nationalism during periods of crisis and/or austerity measures in contemporary Europe"--
Keywords: Europäische Union; Collective memory / Europe; Nationalism / Europe; Group identity / Europe; Kollektives Gedächtnis; Geschichtsbewusstsein; Nationalismus; Osteuropa; Aufsatzsammlung